(untitled) (Agroindustrial Science, 2022)
The objective of the study was to evaluate the effect of the application of two organic amendments (biol and liquid carbon) on the cadmium of the soil, leaves and almonds of the cocoa crop, plantation CCN-51 (Theobroma cacao L.), five years of production, in the province of Huamalíes, Huánuco region, Peru. The research used a completely randomized block design (RCDB) with a factorial arrangement of 3 x 3 + 1 additional control. Total cadmium in the soil, leaves and cocoa beans was evaluated. The lowest content of total cadmium in the soil was determined when applying 50 L/ha of biol (0.13 ppm of cadmium) and when applying 4 L/ha of liquid carbon (0.12 ppm of cadmium); while, without the application of organic liquid amendments, the average value was 0.36 ppm of cadmium. Likewise, T5 (80 L/ha of biol + 4 L/ha of liquid carbon) reduces the available cadmium content of the soil by 73.58%; while T4 decreases the cadmium content in leaves and almonds by 43.83% and 62.96%, respectively.